118k views
9 votes
F(x) = 2x^3 + 5x^2 -6x-7 g(x) = 2x-3 find (f - g) (x)

F(x) = 2x^3 + 5x^2 -6x-7 g(x) = 2x-3 find (f - g) (x)-example-1
User Saadeez
by
5.2k points

1 Answer

9 votes

Given:

The function are:


f(x)=2x^3+5x^2-6x-7


g(x)=2x-3

To find:

The function (f-g)(x).

Solution:

We have,


f(x)=2x^3+5x^2-6x-7


g(x)=2x-3

We need find (f-g)(x).


(f-g)(x)=f(x)-g(x)


(f-g)(x)=2x^3+5x^2-6x-7-(2x-3)


(f-g)(x)=2x^3+5x^2-6x-7-2x+3

On combining like terms, we get


(f-g)(x)=2x^3+5x^2+(-6x-2x)+(-7+3)


(f-g)(x)=2x^3+5x^2-8x-4

Therefore, the correct option is B.

User Yaroslav Lozynskyi
by
4.6k points